2013
DOI: 10.1158/1055-9965.epi-12-1033
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Serum Metabolomics-Based Diagnostic Approach to Pancreatic Cancer

Abstract: Background: To improve the prognosis of patients with pancreatic cancer, more accurate serum diagnostic methods are required. We used serum metabolomics as a diagnostic method for pancreatic cancer.Methods: Sera from patients with pancreatic cancer, healthy volunteers, and chronic pancreatitis were collected at multiple institutions. The pancreatic cancer and healthy volunteers were randomly allocated to the training or the validation set. All of the chronic pancreatitis cases were included in the validation s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 39 publications
14
146
1
1
Order By: Relevance
“…Recently, some panels of new potential biomarkers based on biological, immunological, and genetic changes of PC using blood samples or body fluids, such as urine and saliva, have been reported. A serum metabolomics‐based diagnostic model and salivary transcriptomic biomarkers for diagnosis of resectable PC are reported to possess higher accuracy than conventional markers 45, 46. Fukutake et al .…”
Section: Potential Biomarkers For Early Diagnosismentioning
confidence: 99%
“…Recently, some panels of new potential biomarkers based on biological, immunological, and genetic changes of PC using blood samples or body fluids, such as urine and saliva, have been reported. A serum metabolomics‐based diagnostic model and salivary transcriptomic biomarkers for diagnosis of resectable PC are reported to possess higher accuracy than conventional markers 45, 46. Fukutake et al .…”
Section: Potential Biomarkers For Early Diagnosismentioning
confidence: 99%
“…A feasibility study attempting to identify pancreatic cancer using an elevated CA19-9 and the referral for EUS showed that in 546 patients with a single first degree relative with pancreatic cancer, only 1 pancreatic adenocarcinoma was found at a cost of more than $40,000 [10]. CA 19-9 in combination with newer screening modalities such as microRNA biomarkers in whole blood and serum metabolism profiling has shown improved sensitivity however their role in clinical practice has not yet been clarified [28,29].…”
Section: Screening Toolsmentioning
confidence: 99%
“…The concept of altered cancer metabolism, described as the Warburg effect, where cancer cells preferentially convert glucose into lactate even in the presence of abundant oxygen, has been validated in a variety of cancer subtypes [55][56][57][58]. This serves as the support for using [18F]-fluorodeoxyglucose (FDG) enhanced positron emission tomography (FDG-PET) imaging of solid tumours, which shows glycolytic flux [54,59].…”
Section: Imaging Biomarkersmentioning
confidence: 99%